High-performance supercapacitors and batteries derived from activated banana-peel with porous structures. (20th December 2016) - Zhang, Yunya; Gao, Zan; Song, Ningning; Li, Xiaodong
Graphical abstract: Highlights: Activated banana peel (ABP) exhibited hierarchically porous structures. The ABP-based supercapacitors exhibited high energy density and power density. Ni(NO3 )2 treatment created nanopores and Ni/graphene core/shell particles. The ABP-derived Li-S batteries displayed superior capacity and cycling ability. Abstract: Carbonaceous materials derived from non-renewable and non-sustainable graphite and fossil fuels have been widely used in building supercapacitor and battery electrodes but the mining and fabrication processes are often hazardous and contaminative. Therefore, to derive activated carbon from renewable bio-mass materials is environmentally and socially significant. Here a unique and innovative solution is proposed to produce supercapacitors and batteries from banana peels. Banana peel, which is one of the most abundant and accessible bio-wastes, naturally processes hierarchically porous structure, making activated banana peel (ABP) an ideal backbone for loading electroactive nanomaterials. The ABP derived asymmetric supercapacitors exhibited superior rate capacity and cyclic ability, as well as a synergetic enhancement of energy density and power density because the interconnected porous structure stimulated the formation of urchin-like NiCo2 O4 particles, prevented the aggregation of NiCo2 O4 nanowires, and enhanced the electrolyte accessibility. Orderly arranged nanopores with unique Ni/graphene core/shell nanoparticles were created by annealing the Ni(NO3 )2 solution-treated ABP. The lithium-sulfur (Li-S) batteries built by the ABP/Ni/graphene hybrid achieved exceptionally high electrochemical properties in terms of specific capacitance (1260.3 mAh g −1 at 0.2C), rate capability, and cycling robustness.